Implementation of Total Quality Management in Higher Education A conceptual framework (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Purpose – TQM in Higher Education has demonstrated remarkable effectiveness in driving substantial improvements across various dimensions of educational institutions. There is a significant opportunity to gain valuable insight into the global competitiveness of academic institutions through a study of QAPs (Quality Assurance Practices) in Higher Education Institutions (HEIs). The research assesses the impacts of QAPs on higher education and their outcomes facilitated by the HEIs to prepare students for employability.Design/methodology/approach – The study employs an exploratory research approach. QAPs from various assessment, accreditation, and ranking bodies were assessed, and variables were gathered for the study. After adopting the common-sense method, eight independent variables were identified that potentially influence the success of TQM and student employability in HEIs. The study's eight independent variables are governance leadership, student support progression, research consultancy extension, curriculum aspects, teaching, learning & evaluation, innovative practices, infrastructure learning resources, and collaboration, with two dependent variables, TQM effectiveness, and student employability, finalized.Findings – The findings reveal that the QAPs of HEIs, such as Governance Leadership, Student Support Progression, Research Consultancy Extension, Curriculum Aspects, Teaching Learning Evaluation, Innovative Practices, Infrastructure Learning Resources, and Collaboration, influence TQM Effectiveness. The study also supports that student employability is an outcome of the TQM effectiveness influenced by the QAPs of HEIs, representing a paradigm of educational excellence and advancing knowledge, societal contribution, and building an employable global workforce.Practical Implications – The article explores the dimensions of QAPs of higher education assessment, accreditation, and ranking bodies from India and a few global regulators. The study reveals that the HEIs are committed to upholding academic standards and ensuring the delivery of high-quality education. The HEIs often cater to a diverse student population by adapting to local regulations and policies. The study emphasizes the need for continuous assessment and improvement strategies to meet the evolving needs of students and other stakeholders globally. The research findings can help HEIs produce the intended results while meeting and exceeding the expectations of their stakeholders. It can also assist institutions to improve their reputations.Originality/value – This is possibly a one-of-a-kind study that used a methodology to evaluate the QAPs of assessing, accrediting, and ranking agencies of HEIs. The findings may assist higher education institutions in maintaining their global competitiveness.